Obturator Bypass with Bovine Carotid Artery Graft: A Novel Twist to a Traditional Technique - Sarah Brown; Christopher Esper; Jon Henwood (Case Reports in Surgery)
When managing an infected groin, though rarely performed, a transobturator bypass remains an important alternative in the armament of a vascular surgeon. Autologous vein and synthetic PTFE are known conduit options for obturator bypasses, although the advantage of utilizing an autologous biological conduit when dealing with infection may not be an option for every patient. On literature review, bovine carotid grafts have been used in infrainguinal revascularizations with comparable results to autologous vein; however, no cases can be found for its use in obturator bypass thus far.